User Requirements in Enterprise Resource Planning Systems Adoption: A Case of Botswana’s Higher Institutions - Moya, Lingani; Chukwuere, Joshua (Journal of Information System and Informatics, 2023)
ERP systems are the largest software applications adopted by universities, along with quite significant investments in their implementation. However, unlike other applications, limited research has been conducted regarding the application of this system in higher education in Botswana. This study aims to identify user requirements in the adoption of enterprise resource planning (ERP) systems in Botswana’s higher education institutions. This study was conducted in three higher education institutions in Botswana. This study adopted the quantitative methodology of using surveys to understand ERP adoption in higher education and proposed a model that could be used to guide business information systems requirements to appropriate ERP systems in a higher educational environment. Based on the findings, the study proposed a conceptual model of ERP system adoption in higher education institutions using six success dimensions. The six success dimensions are user requirements, user satisfaction, information quality, service quality, institutional impact, system quality, and faculty/management impact. Only information quality was rejected from the model. The six success dimensions are the basis through which a higher education institution can understand user requirements in implementing an effective ERP.